2010
DOI: 10.5902/198050981845
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e nutrição mineral do nim (<i>Azadirachta indica</i> A. Juss.) e cinamomo (<i>Melia azedarach</i> Linn.) submetidos à salinidade.

Abstract: Este trabalho teve como objetivo verificar os efeitos da salinidade do solo no crescimento e no acúmulo de macronutrientes e de sódio em nim (Azadirachta indica) e cinamomo (Melia azedarach). O experimento foi disposto em delineamento experimental inteiramente casualizado em arranjo fatorial 2 x 4, sendo duas espécies (nim e cinamomo) e quatro níveis de salinidade (Condutividade elétrica (C.E.) 0,49 (solo não salino); 4,15; 6,33 e 10,45 dS m-1), com 4 repetições. As plantas cresceram inicialmente em tubetes e,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
(7 reference statements)
1
6
0
11
Order By: Relevance
“…Freire et al (2010), studying the effects of irrigation water salinity on neem plants, observed that plant growth was also hampered with the increase in the electrical conductivity of the irrigation water. Gabriel et al (2012) observed that the leaching of salts from the root zone allowed a higher gain of biomass in maize plants, which was also observed in noni plants under saline conditions in the presence of salt leaching through the drainage.…”
Section: Resultsmentioning
confidence: 99%
“…Freire et al (2010), studying the effects of irrigation water salinity on neem plants, observed that plant growth was also hampered with the increase in the electrical conductivity of the irrigation water. Gabriel et al (2012) observed that the leaching of salts from the root zone allowed a higher gain of biomass in maize plants, which was also observed in noni plants under saline conditions in the presence of salt leaching through the drainage.…”
Section: Resultsmentioning
confidence: 99%
“…Pela sua rusticidade se desenvolve em solos fisicamente degradados, exige pH entre 6 e 7 mas também tolera amplitudes dessa variável de 3 a 9, cresce e produz em regiões com pluviosidades oscilando de 400 a 800 mm e suporta longos períodos de estiagem (Freire et al, 2010).…”
Section: Introductionunclassified
“…Entretanto, no que se refere ao crescimento inicial e ao seu estabelecimento em ambientes salinos, as informações ainda são escassas na literatura. Neste sentido, Gurumurthy et al (2007), Cha-Um & Kirdmanee (2008) e Freire et al (2010) constataram que, durante a formação de mudas e até o primeiro ano, o nim se comporta como moderadamente tolerante e moderadamente sensível à salinidade.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Since the beginning of the 21 st century, scientific information about the use of native and exotic species (mainly non-food species) has been growing, aiming to exploit their tolerance to salinity as an alternative to reforestation or the physical and chemical recovery of degraded soils contaminated by salts (GURUMURTHY et al, 2007;FREIRE et al, 2010;GHRAB et al, 2013;ISLA;GUILLÉN;ARAGÜÉS, 2014).…”
Section: Introductionmentioning
confidence: 99%